THE IMPLEMENTATION OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) METHOD IN IMPROVING STUDENT’S READING COMPREHENSION AT SMP MUHAMMADIYAH 2 DEPOK SLEMAN - Irfun Irfun (CV. ADIBA AISHA AMIRA, 2022)
The objective of this study is to find out whether there is a significant difference in reading comprehension between students who are taught by using cooperative integrated reading and composition (CIRC) and without using it. CIRC was compared with conventional method in teaching-learning process. This study is a quasi-experimental design (Creswell, 2012). The technique sampling of this study is purposive sampling. The subjects of this study were eight grade students of SMP Muhammadiyah 2 Depok, which consisted of 90 students. They were divided into three classes. Two classes were taken. Class A was as an experimental class and class B was as the control class. The pre-test was given to both classes (experimental class and control class) before the treatment. During the study, the students of the experimental class were taught by using CIRC whereas the control class was taught by using conventional method. The teaching-learning process was carried out for five weeks. At the end of the experiment, the post-test was given to both classes. The data were analyzed by using SPSS14 (Independent Samples- Test). The finding revealed that there is a significant difference between CIRC and conventional method in improving students' reading comprehension. The experimental class is proven to be more effective than the conventional method